2011
DOI: 10.1183/09031936.00023211
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cost and performance of light-emitting diode microscopy in HIV–tuberculosis-co-infected patients

Abstract: Light-emitting diode (LED) microscopy has recently been endorsed by the World Health Organization (WHO). However, it is unclear whether LED is as accurate and cost-effective as Ziehl–Neelsen (ZN) microscopy or mercury vapour fluorescence microscopy (MVFM) in tuberculosis (TB)–HIV-co-infected subjects. Direct and concentrated sputum smears from TB suspects were evaluated using combinations of LED microscopy, ZN microscopy and MVFM. Median reading time per slide was recorded and a cost analysis performed. Mycoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 10 publications
5
36
0
1
Order By: Relevance
“…Nonetheless, SROC plots suggested that liquid culture reference standard was associated with higher diagnostic accuracy of LED-FM (see online supplementary material). Studies using culture on one specimen (n=7) [14-17, 19, 22, 23] had a lower pooled specificity (94.7%) and a higher sensitivity (70.0%) compared with studies using more than one specimen (n=6) [13,15,18,20,21,24] (98.5% and 61.1%, respectively), although the differences were not statistically significant. SROC plots suggested that culture reference based on more than one specimen improved the diagnostic accuracy of LED-FM, although associated with increasing heterogeneity in both sensitivity and specificity estimates of the LED-FM (see online supplementary material).…”
Section: Subgroup Accuracy Analysismentioning
confidence: 64%
See 3 more Smart Citations
“…Nonetheless, SROC plots suggested that liquid culture reference standard was associated with higher diagnostic accuracy of LED-FM (see online supplementary material). Studies using culture on one specimen (n=7) [14-17, 19, 22, 23] had a lower pooled specificity (94.7%) and a higher sensitivity (70.0%) compared with studies using more than one specimen (n=6) [13,15,18,20,21,24] (98.5% and 61.1%, respectively), although the differences were not statistically significant. SROC plots suggested that culture reference based on more than one specimen improved the diagnostic accuracy of LED-FM, although associated with increasing heterogeneity in both sensitivity and specificity estimates of the LED-FM (see online supplementary material).…”
Section: Subgroup Accuracy Analysismentioning
confidence: 64%
“…Lumin™ (LW Scientific, Lawrenceville, GA, USA), evaluated in five studies [13,18,[20][21][22], was the most commonly used device and displayed the best diagnostic performance on the SROC plots (see online supplementary material). Performance evaluations of all the other devices were based on fewer than four studies.…”
Section: Subgroup Accuracy Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It can be performed on un-centrifuged specimens at the point of care. The introduction of the low cost light-emitting diode (LED) microscopy with the benefit of fluorescence microscopy without the associated operational requirements, has offered a new tool for POCT-TB [1]. More recently, the processing of serial sputum specimen examinations in the front-loaded microscopy approach focuses on collecting several specimens during one visit [2].…”
Section: Introductionmentioning
confidence: 99%